2000
DOI: 10.1161/01.atv.20.3.823
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus

Abstract: Abstract-Previously diagnosed diabetes mellitus, newly diagnosed diabetes mellitus, and impaired glucose tolerance are important determinants of the risk of clinical cardiovascular disease (CVD). We have evaluated the relation of patients with subclinical CVD, diabetes, and impaired glucose tolerance and "normal" subjects and the risk of clinical CVD in the Cardiovascular Health Study. Diabetes (1343), impaired glucose tolerance (1433), and normal (2421)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(56 citation statements)
references
References 44 publications
3
51
0
2
Order By: Relevance
“…Recently, we have shown that subclinical CVD is the primary determinant of incident clinical CVD in individuals with glucose disorders (2). Considering the high prevalence of isolated subclinical CVD among participants with glucose disorders, efforts at CVD risk factor reduction in those without clinical CVD seem warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that subclinical CVD is the primary determinant of incident clinical CVD in individuals with glucose disorders (2). Considering the high prevalence of isolated subclinical CVD among participants with glucose disorders, efforts at CVD risk factor reduction in those without clinical CVD seem warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical disease is a strong risk factor for clinical CVD (1)(2)(3)(4). Knowledge of the prevalence of subclinical disease in asymptomatic patients is therefore of interest to the clinician for the purposes of risk stratification.…”
mentioning
confidence: 99%
“…Moreover, in uncomplicated well-controlled type 2 diabetes, LV dysfunction detected by echocardiography has been associated with impaired functional capacity observed in these patients [2]. A follow-up study over 6.4 years demonstrated that diabetic subjects had a higher prevalence of clinical and subclinical cardiovascular disease at baseline, and the presence of subclinical cardiovascular disease and diabetes was associated with significantly increased adjusted relative risk of death, relative risk of incident coronary heart disease, and incident myocardial infarction [3]. Thus, subclinical cardiovascular disease is an important determinant of clinical cardiovascular disease among diabetic patients, and the detection of subclinical cardiovascular disease in these patients may provide an approach for identifying high-risk individuals who may benefit from earlier and more active intervention to prevent clinical disease.…”
Section: Introductionmentioning
confidence: 99%
“…Even subjects with milder disturbances in glucose metabolism, such as IGT, are at an increased risk of cardiovascular disease [3,4].…”
Section: Introductionmentioning
confidence: 99%